FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Akiah, Siti; Puspita, Dian Puji; Ramashar, Wira (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to analyze the factors that influence audit delay. The population in this research is the LQ 45 companies listed on the Indonesia Stock Exchange totaling 45 companies with sampling using saturated sampling so that the research sample amounts to 225 data samples. The data collection technique uses a quantitative method approach, namely using documentation from the company. Data analysis used multiple linear regression analysis and was processed using the Statistical Package for Social Science (SPSS) version 27 program. The research results found that company size, solvency and profitability had an effect on audit delay in LQ 45 companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Keywords: Company Size, Solvency, Profitability, Audit Delay